Synthesis and characterization of EuBa2Ca2Cu3O9-x: The influence of temperature on dielectric properties and charge transport mechanism - Ozdemir, Z. Guven; Kilic, M.; Karabul, Y.; Misirlioglu, B. Sungu; Cataltepe, O. Aslan; Icelli, O. (ELSEVIER SCI LTD, 2017)
High dielectric constant materials have a crucial importance for various microelectronic applications such as memory devices, supercapacitors etc. Among other insulators, perovskite structured oxide materials attract great interest not only for their high dielectric constants but also their unique electrical and magnetic properties such as superconductivity etc. From this point of view, a new Europium based copper oxide layered material with perovskite structure (EuBa2Ca2Cu3O9-x coded as Eu-1223) has been synthesized by solid state reaction method in this work. The physical and chemical properties of Eu-1223 have been determined by FTIR, SEM, XRF, XRD, TGA and DTA techniques. The influence of temperature on impedance and dielectric properties of Eu-1223 has been investigated by impedance spectroscopy measurements performed within the frequency interval of 5 Hz-13 MHz between 298 K and 408 K temperatures. It has been found that the Eu-1223 material has high dielectric constants at each temperature operated. In addition, Eu-1223 sample behaves as a colossal dielectric material up to 300 kHz for 408 K due to observation of dielectric constant values which are greater than 10(3). Furthermore, it has been revealed that Eu-1223 material can be used as thermally sensitive resistors in electronic circuits due to its decreasing resistance with increasing temperature. Moreover, it has been observed that the relaxation frequency of the system shifts from 46.5 kHz (low frequency radio wave band) to 1.57 MHz (mid frequency radio wave band) as the temperature increasing from 298 K to 408 K. According to dc conductivity investigations, the variation of de conductivity with the inverse of temperature satisfies linear relationship that indicates a thermally activated nearest neighbor hopping conduction. On the other hand, it has been determined that ac conductivity has frequency dependent relation which obeys omega(s) for the high frequency region. Furthermore, the frequency exponent, s, which takes values between 0.7 and 0.4, shows a decreasing behavior with increasing temperature. In conclusion, ac charge transport mechanism has been predicted as correlated barrier hoping for Eu-1223.
Keywords: Powders: Solid state reaction; Dielectric properties; Electrical conductivity; Perovskites; Thermistors; CONSTANT; RELAXATION; PEROVSKITE; CONDUCTIVITY; IMPEDANCE; Engineering; Materials Science; Physics